2023
DOI: 10.1371/journal.pone.0281980
|View full text |Cite
|
Sign up to set email alerts
|

Predicting areas important for ecological connectivity throughout Canada

Abstract: Governments around the world have acknowledged that urgent action is needed to conserve and restore ecological connectivity to help reverse the decline of biodiversity. In this study we tested the hypothesis that functional connectivity for multiple species can be estimated across Canada using a single, upstream connectivity model. We developed a movement cost layer with cost values assigned using expert opinion to anthropogenic land cover features and natural features based on their known and assumed effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…by the degree to which they facilitate or impede movement (McRae et al, 2008). For the following analyses, we used the 300-m resolution cost surface of Canada produced by Pither et al (2023), which classifies the landscape according to a cost scheme using 4 values including 1 (low cost), 10, 100, and 1000 (high cost) (Table 1). Bowman et al (2020) showed that current density maps are not sensitive to the absolute costs of a cost surface provided that costs are in the correct rank order.…”
Section: Cost Surface and Nodesmentioning
confidence: 99%
See 4 more Smart Citations
“…by the degree to which they facilitate or impede movement (McRae et al, 2008). For the following analyses, we used the 300-m resolution cost surface of Canada produced by Pither et al (2023), which classifies the landscape according to a cost scheme using 4 values including 1 (low cost), 10, 100, and 1000 (high cost) (Table 1). Bowman et al (2020) showed that current density maps are not sensitive to the absolute costs of a cost surface provided that costs are in the correct rank order.…”
Section: Cost Surface and Nodesmentioning
confidence: 99%
“…This approach, which has been used in many other studies, models landscape connectivity based on degree of naturalness or human modification and makes the assumption that more natural landscapes are less costly for many animals to move through and better facilitate ecological processes (Krosby et al, 2015;Spencer et al, 2010;Theobald et al, 2012). Pither et al (2023) built their cost surface using the most up-to-date spatial data layers including the Canadian Human Footprint (Hirsh-Pearson et al, 2022) and an updated national road layer (Poley et al, 2022). We modified the 300-m cost surface of Pither et al (2023) by adding a fifth lowest cost, which we assigned to natural areas within protected area boundaries under the assumption that these areas are less costly to move through than natural areas outside park boundaries (Spencer et al, 2010; Table 1).…”
Section: Cost Surface and Nodesmentioning
confidence: 99%
See 3 more Smart Citations